2019
DOI: 10.1002/erv.2705
|View full text |Cite
|
Sign up to set email alerts
|

Is food addiction a predictor of treatment outcome among patients with eating disorder?

Abstract: Objectives:The study aimed to examine whether food addiction (FA) was associated with greater severity in both binge eating disorders (BED) and bulimia nervosa and, therefore, to determine if FA was predictive of treatment outcome.Method: Seventy-one adult patients with bulimia nervosa and BED (42 and 29, respectively) participated in the study. FA was assessed by means of the Yale Food Addiction Scale. Results:The results confirmed a high prevalence of FA in patients with binge disorders (around 87%) and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 64 publications
7
24
0
Order By: Relevance
“…The present review suggests that it would be effective to identify FA phenotypes based on the presence of other psychiatric disorders such as ED, AUD/SUD, PTSD, depression, anxiety, and ADHD as part of a comprehensive biopsychosocial assessment, and to assign nutrition treatment based on the relative strength of the FA signal amidst the noise (true versus false positive). Recent studies have identified different phenotypic characterizations of the FA construct [ 60 , 61 , 202 , 203 ]. However, Table 1 suggests a guide for clinicians to consider in settings where the use of extensive validated instruments is not always practical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present review suggests that it would be effective to identify FA phenotypes based on the presence of other psychiatric disorders such as ED, AUD/SUD, PTSD, depression, anxiety, and ADHD as part of a comprehensive biopsychosocial assessment, and to assign nutrition treatment based on the relative strength of the FA signal amidst the noise (true versus false positive). Recent studies have identified different phenotypic characterizations of the FA construct [ 60 , 61 , 202 , 203 ]. However, Table 1 suggests a guide for clinicians to consider in settings where the use of extensive validated instruments is not always practical.…”
Section: Discussionmentioning
confidence: 99%
“…BED + FA requires tailored treatment approaches [ 60 ]. One study suggested that when diagnostic subtypes are considered separately, FA is associated with a poor prognosis in the BED group [ 61 ]. It is possible that poor BED outcomes stem from the transdiagnostic assumption that BED patients do not need to emphasize the quality of their food (“it’s not about the food”).…”
Section: Eating Disordersmentioning
confidence: 99%
“…Other studies had already associated negative urgency with bingeing (Claes et al, 2015; Racine et al, 2015; Steward et al, 2017) and it was the only predictor of food addiction (FA) in patients with binge eating symptomatology (Wolz, Granero, & Fernández‐Aranda, 2017). This is important because FA is a highly comorbid condition in patients with BED which may contribute to greater general and eating disorder‐specific psychopathology (Linardon & Messer, 2019) and could be a predictor of treatment outcome in BED (Romero et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a number of studies have investigated the association between food addiction and symptoms of mental disorders, especially depression, anxiety, and eating disorders, and have quite consistently found positive associations (please see reviews by Burrows et al (Burrows, Kay‐Lambkin, Pursey, Skinner, & Dayas, 2018) and Meule and Gearhardt (Meule & Gearhardt, 2019)). However, the few studies that are based on clinical samples have almost exclusively focused on eating disorders of the bingeing subtype (bulimia nervosa and binge‐eating disorder) (Granero et al, 2014, 2018; Hilker et al, 2016; Ivezaj, Wiedemann, Lawson, & Grilo, 2019; Jiménez‐Murcia et al, 2019; Romero et al, 2019; Wolz et al, 2016; Wolz, Granero, & Fernandez‐Aranda, 2017) with the exception of two studies in schizophrenia (Goluza, Borchard, Kiarie, Mullan, & Pai, 2017; Kucukerdonmez, Urhan, Altin, Haciraifoglu, & Yildiz, 2019) and one in ADHD (Brunault et al, 2019). All of these studies have reported that the prevalence of food addiction was higher among individuals with mental disorders compared to (general population) controls.…”
Section: Introductionmentioning
confidence: 99%